2009
DOI: 10.1128/iai.00851-09
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetiiIsolates Cause Genogroup-Specific Virulence in Mouse and Guinea Pig Models of Acute Q Fever

Abstract: Q fever is a zoonotic disease of worldwide significance caused by the obligate intracellular bacterium Coxiella burnetii. Humans with Q fever may experience an acute flu-like illness and pneumonia and/or chronic hepatitis or endocarditis. Various markers demonstrate significant phylogenetic separation between and clustering among isolates from acute and chronic human disease. The clinical and pathological responses to infection with phase I C. burnetii isolates from the following four genomic groups were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
109
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(117 citation statements)
references
References 43 publications
4
109
2
2
Order By: Relevance
“…Different isolates of C. burnetii are associated with unique disease states characterized by distinct pathological features. For instance, the Dugway (D) rodent isolate is avirulent compared to NMI (32), whereas the Graves (G) and Kearns (K) isolates establish an infection characterized by less inflammation and dissemination (33). Comparison of these different isolates revealed that many effector proteins are intact in specific group isolates but disrupted in other isolates, suggesting that different effector proteins may be responsible for different host cell responses and consequently for distinct disease states (12,21,34).…”
Section: Resultsmentioning
confidence: 99%
“…Different isolates of C. burnetii are associated with unique disease states characterized by distinct pathological features. For instance, the Dugway (D) rodent isolate is avirulent compared to NMI (32), whereas the Graves (G) and Kearns (K) isolates establish an infection characterized by less inflammation and dissemination (33). Comparison of these different isolates revealed that many effector proteins are intact in specific group isolates but disrupted in other isolates, suggesting that different effector proteins may be responsible for different host cell responses and consequently for distinct disease states (12,21,34).…”
Section: Resultsmentioning
confidence: 99%
“…5,22,24,25 In the guinea pig model, severe acute pneumonia developed in animals when they were infected with C. burnetii strains harboring the QpH1 plasmid (Nine Mile, African, and Ohio strains), mild to moderate disease when they were infected with plasmid-less C. burnetii strains (Q217 and Q212 strains), and were asymptomatic when they were infected with C. burnetii strains harboring the QpRS (Priscilla) or QpDG (Dugway) plasmids. 23 Only C. burnetii strains carrying the QpH1 or the QpDV plasmid have been associated with acute Q fever in humans. 26 Because the clinical picture and severity of acute Q fever is related to the strain, the incidence of diagnosed acute Q fever does not reflect the actual incidence of Q fever.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the inoculum can influence the clinical picture and the degree and duration of the clinical response in acute Q fever, as described in several animal models. 20,22,23 A murine model of aerosol infection has shown that only high inocula of the C. burnetii strain Nine Mile I ( 10 8 bacteria) cause pneumonia. 22 However, different clinical forms of acute Q fever are also dependent on the strain.…”
Section: Discussionmentioning
confidence: 99%
“…All genogroups of C. burnetii phase I isolates produced disease in the SCID mouse model. 21 Comparative virulence of phase I and II C. burnetii in immunodeficient mice has also been described in Reference 13. Cloned NMI and NMIIC4 were used in SCID and SCIDbg (lacking T, B, and NK cells) mice.…”
mentioning
confidence: 99%